Volume 6: Materials and Fabrication, Parts a and B 2012
DOI: 10.1115/pvp2012-78393
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Long-Term Creep Strength of Welded Joints of ASME Grades 91, 92 and 122 Type Steels

Abstract: Creep rupture data of welded joints of ASME Grades 91, 92 and 122 type steels have been collected and long-term creep rupture strength of the materials has been evaluated. Similar study was conducted by the SHC Committee in 2004 and 2005, therefore, the evaluation of the creep rupture strength was conducted with emphasis on the long-term creep rupture data obtained after the previous study, in addition to discussion of the effects of product form, welding procedure and test temperature etc. on the creep streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The grain structure in a PT, OT-PT, PT-PT, or CT-PT region can be varied from a completely reaustenitized refined grain structure upon peak temperatures of close to the Ac 3 temperature to a partially reaustenitized grain structure upon peak temperatures of close to the Ac 1 temperature, which is consistent with the observations from the existing literature. [15,25] The partially reaustenitized matrix, which exhibits significant microstructural heterogeneities, has been linked to the presence of HAZ failures in a recent article. [26] Further work is under way to link the observations provided here to actual longterm creep test HAZ failures in an effort to better establish the influence of the welding thermal cycle on …”
Section: Microstructural Influence On Creep Propertiesmentioning
confidence: 99%
“…The grain structure in a PT, OT-PT, PT-PT, or CT-PT region can be varied from a completely reaustenitized refined grain structure upon peak temperatures of close to the Ac 3 temperature to a partially reaustenitized grain structure upon peak temperatures of close to the Ac 1 temperature, which is consistent with the observations from the existing literature. [15,25] The partially reaustenitized matrix, which exhibits significant microstructural heterogeneities, has been linked to the presence of HAZ failures in a recent article. [26] Further work is under way to link the observations provided here to actual longterm creep test HAZ failures in an effort to better establish the influence of the welding thermal cycle on …”
Section: Microstructural Influence On Creep Propertiesmentioning
confidence: 99%
“…The temperature in the header component is kept at 600 • C during the whole loading procedure. Remark: In [16], the creep rupture data for compound crossweld specimens are reported. Strictly speaking, the material parameters determined based on these testing data are not exactly the material parameters of the HAZ, because the weld joints also contain the base and the weld metal regions.…”
Section: Simulation Of the Type-iv Creep Testmentioning
confidence: 94%
“…To achieve a more accurate simulation, a finer mesh has been used in the HAZ. The material parameters (related to creep strain) identified for P92 weld joints (by using the experimental results reported in [16]) are applied in the HAZ, while the material in the other part of the header component is supposed to be the general P92 steel. The loading procedure of the type-IV creep test is illustrated in Fig.…”
Section: Simulation Of the Type-iv Creep Testmentioning
confidence: 99%
See 1 more Smart Citation
“…MARBN exhibits not only much higher creep rupture strength of base metal than P92 but also substantially no degradation in creep rupture strength of welded joints compared with base metal, indicating no Type IV fracture. It has been reported that Gr.91, Gr.92 and Gr.122 exhibit the significant degradation in creep rupture strength of welded joints due to Type IV fracture in HAZ at temperatures above 600 o C [16]. Fig.15 Creep rupture data for base metal and welded joints of MARBN and P92 at 650 o C.…”
Section: Suppression Of Type IV Fracture In Haz Of Welded Jointsmentioning
confidence: 97%